A Multidisciplinary Standardized Patient Simulation for Using Trauma-Informed Care for Pregnant Patients - Danielle Nichole Olson; Anna Brandt; Sarah Greywitt; Kelly S. Gibson (Association of American Medical Colleges, 2024)
Introduction Pregnant patients with prior traumatic experiences and their providers face challenges during prenatal care, peripartum, and postpartum. To date, no structured simulations have been published focused on improving care for patients in subsequent pregnancies. Methods This multidisciplinary simulation included trainees and providers. Standardized patients were used. The patient was multiparous with a remote history of substance use and was initiating prenatal care late due to concerns related to the prior traumatic experience of losing custody of a newborn after a Department of Children and Family Services report had been opened in a prior pregnancy. Simulation participants completed the prenatal intake and counseling regarding this prior experience. Debriefing sessions reviewed critical actions, including collecting a history, empathizing with the patient, praising efforts to maintain pregnancy health, discussing available resources, constructing a plan for care, and utilizing motivational interviewing techniques. The simulation and debriefing sessions were allotted 30 minutes total. Pre- and postsimulation surveys evaluated for increased comfort and knowledge in caring for patients with prior traumatic experiences. Results Simulation participants included obstetrics and gynecology students and residents, nurses, advanced practice providers, generalist attendings, and maternal fetal medicine fellows and attendings. Sixty participants completed the presimulation survey. Twenty-seven (45%) completed the postsimulation survey. Responses were paired for analysis. Scores on knowledge assessments improved postsimulation (p = .001). Responses suggested increased comfort in discussing prior traumatic experiences (p = .13). Discussion This simulation led to improved background knowledge and comfort regarding providing trauma-informed care during pregnancies impacted by a prior traumatic event.